Pengaruh Good Corporate Governance dan Ukuran Perusahaan Pada Kinerja Keuangan Perusahaan Perbankan - Wahyuni, Ni Ketut Sri; Sukartha, I Made (E-Jurnal Akuntansi, 2019)
Bank financial performance is an illustration of the level of success achieved by the bank in its operational activities. The purpose of this study is to find out the empirical evidence of the effect of GCG and company size on the financial performance of banking companies. The technique for determining purposive sampling. The total sample in this study was 10 samples with 45 observation for 5 years. The data analysis multiple linear regression analysis. The results of the study prove that good corporate governance GCG ernance has a positive effect on the financial performance of banking companies. The size of the company has a positive effect on the financial performance of banking companies. The results of this study are expected to be useful for banking companies to continue to strive to implement all components of GCG and obtain a reliable CGPI rating so that it becomes a reference for investors. Keywords : Good Corporate Governance; Company Size and Financial Performance.